Beyond the gimmick: How affective responses drive brand attitudes and intentions in augmented reality marketing - Vera Zanger; Martin Meißner; Philipp A. Rauschnabel (Psychology & Marketing, 2022)
According to recent research in augmented reality (AR) marketing, AR-based product presentations have the potential to create extraordinary shopping experiences across the customer journey. However, the mechanisms that drive key marketing metrics, such as brand evaluations or purchase intentions, are yet to be thoroughly understood. Drawing on the Affect-as-Information Theory, this study placed affective responses, such as customers' enjoyment and inspiration, at the center of decision-making and conducted two online experiments to empirically investigate (1) the differences in the intensity of affective responses between AR and non-AR, (2) the interplay between affective and cognitive responses in shaping behavioral outcomes, and (3) the moderating role of customer-specific factors (customers' AR familiarity and product knowledge) on affective responses. According to the results, although the affective responses increase purchase and word-of-mouth intentions directly as well as indirectly through product/brand attitudes, AR does not per se guarantee more positive affective responses; rather, they depend on the technical implementation of AR features and customers' AR expertise, among others.
Keywords: 650; AR marketing; augmented reality; brand attitude; branding; enjoyment; inspiration; purchase intention; word-of-mouth